On the use of vitamins in the nutrition of professional athletes - R. М. Radzhabkadiev; O. A. Vrzhesinskaya; V. M. Kodentsova (National Electronic Information Consortium (NEICON), 2020)
Objective: assessment of the vitamin content in the basic and supplementary diets of highly qualified athletes in the pre-competition period of sports activities. Materials and methods: 159 highly skilled athletes of both sexes participated in the study (92 men, mean age 21.7 ± 0.8 years, 67 women, 23.1 ± 1.5 years). Studies were carried out on the basis of the Center for Physiotherapy and Sports Medicine of FMBA. The content of vitamins in the basic and supplementary diets was estimated by the questionnaire method of 24-hour (daily) nutrition reproduction using the «Album of Food and Food Portions», according to the chemical composition of the actually consumed foods and dishes. The processing and analysis of data was carried out by standard statistical methods. Results: the basic diet of athletes does not provide adequate intake of vitamins. The most pronounced deficiency of B vitamins and vitamin C in the basic diet was noted in female bobsleighs. Only additional consumption of weighty doses of vitamins and specialized products for nutrition of athletes and dietary supplements allows reaching the recommended level. Some sportsmen have exceeded thus consumption of vitamins В1 and В2 with enriching additives in supplements and specialized foodstuff. Conclusions: the groundlessness of using in the diet of athletes excessively high doses of antioxidant vitamins is discussed. Before making a decision about the use of a vitamin supplement and doses of vitamins contained in it, a complete assessment of the individual diet of each athlete is necessary.